In the kingdom of ice : the grand and terrible polar voyage of the USS Jeannette - Sides, Hampton (New York : Doubleday, 2014)
A dramatic account of the ill-fated 19th-century naval expedition to the North Pole cites the contributions of German cartographer August Petermann, New York Herald owner James Gordon Bennett and famed naval officer George Washington De Long in the team's efforts to survive brutal environmental conditions.
Includes bibliographical references (pages 417-451).
Keywords: Bennett, James Gordon, -- 1841-1918.; De Long, George W. -- 1844-1881.; Jeannette (Steamer) -- History; Shipwrecks -- Arctic Ocean -- History -- 19th century; Shipwreck survival -- Arctic Ocean -- History -- 19th century; Shipwreck survival -- Russia (Federation) -- Siberia -- History -- 19th century